Intercultural mediation against the inequality in institutional healthcare access and enjoys. Some considerations about the professional’s praxis in Belgium and Spain - Muñoz Martínez, Ruben (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
The present article summarizes the result of an investigation, carried out in the framework of the author doctoral thesis, on professional’s praxis of intercultural mediation in healthcare that are developed at the present time in Belgiumand Spain. From an anthropological perspective of applied character the most remarkable particularities of these practices are approached in it, in both countries, proposing for the debate their weaknesses and strengths from the point of view of their relevance in the improvement in institutional health care enjoys andaccess of immigrants people.